24.2: Invited Paper: High‐resolution OLED Display Fabricated by Electrohydrodynamic Printing Method. (4th October 2019) - Mu, Lan; Peng, Junbiao
Abstract : A high resolution OLED display was fabricated by using electrohydrodynamic printing method. The printed inks were poly(dibenzothiophene‐S, S‐dioxide‐co‐9, 9‐dioctyl‐2, 7‐fluorene) (PPF‐SO). Both of the printer operation voltage and the solvent properties dominated the ink's printability and printing stability. Line widths of the printed polymers could be controlled. A mono‐color display with resolution over 2000 PPI was realized. The electrohydrodynamic printing method for fabrication of OLED displays will be discussed in the presentation.